The Intertech Equipment for Laboratory Analysis and Scientific Research - Romanov, S.N. (Science and Innovation, 2024)
Intertech is an American corporation which has been supplying instruments for laboratory analysis and scientific research to Ukraine for 15 years. The Corporation is the exclusive dealer of Thermo Fisher Scientific, TA Instruments, and some other companies. Intertech offers instrumentation for elemental and molecular analysis, surface and nanostructure investigation, thermal analysis, sample preparation and provides certified service and methodological support for supplied equipment. There are two service centers in Ukraine, in Kyiv and in Donetsk. More than 100 Ukrainian enterprises use instrumentation supplied by Intertech Corporation including metallurgical, machine-building, chemical, and food industries, academic and research institutions, medical institutions, and environmental inspectorates.